A Social Networking Model for Higher Education in Pakistan - Pervaiz, Sumaiya (Curtin University, 2019)
The objective of this research is to develop a social networking model for the higher education sector of Pakistan. The data was collected by an online survey and interview. The five factors of the model are; social factors, organizational support, technological context, psychological aspects and design aspects of the model exhibited excellent model fit and a strong factor loading. New sub-factors were discovered for the final model and green IT emerged as a new sub-factor in the model.